Epidemiology of respiratory viruses according to age group, 2023–24 winter season, Kyoto, Japan - Yasufumi Matsumura; Masaki Yamamoto; Yusuke Tsuda; Koh Shinohara; Yasuhiro Tsuchido; Satomi Yukawa; Taro Noguchi; Kazuo Takayama; Miki Nagao (Scientific Reports)
Abstract The seasonality and epidemiology of viral acute respiratory infections (ARIs) have changed since the coronavirus disease 2019 pandemic. However, molecular-based ARI surveillance has not been conducted in Japan. We developed a regional surveillance program to define the local epidemiology of ARIs. Between December 2023 and March 2024, 2,992 upper respiratory samples collected from patients suspected of having ARIs at five facilities in Kyoto City, Japan, were tested for SARS-CoV-2, influenza virus, and respiratory syncytial virus (RSV) using RT‒PCR. Samples negative for these viruses were randomly selected for testing with the FilmArray Respiratory Panel, and the detection rates of other viruses were estimated. SARS-CoV-2, influenza virus, and RSV were detected in 598 (20.3%), 165 (5.6%), and 40 (1.4%) of the 2,949 samples with valid RT‒PCR results, respectively. The most prevalent viruses in the < 6, 6–17, 18–64, and ≥ 65 year age groups were rhinovirus/enterovirus, RSV, and SARS-CoV-2; influenza virus, seasonal coronavirus, and rhinovirus/enterovirus; SARS-CoV-2, seasonal coronavirus, and influenza virus; and SARS-CoV-2, seasonal coronavirus, and influenza virus, respectively. Significant differences in the detection rates of these viruses were detected between the age groups. This study highlights the importance of age-stratified molecular-based surveillance for a comprehensive understanding of the epidemiology of ARIs.